Electrospray Ionization Mass Spectrometric Fragmentation of Hydroquinone Derivatives - Caroli-Rezende, M; Almodovar-Fajardo, I (2011)
The fragmentation patterns of nine di-, tri- and tetracyclic hydroquinones with potential antitumor activity were rationalized by invoking competing mechanisms that included sterically accelerated homolytic cleavage, Meerwein-type rearrangements and dehydrations through elimination or intramolecular nucleophilic substitution. © 2010 John Wiley & Sons, Ltd.